Experiências de espiritualidade e os processos criativos dos músicos - Abreu, Eliane Maria de (2010)
This thesis reflects on the possible relation between the creative processes of the musicians and their experiences of spirituality. Our goal is to understand how musician live out their experiences of spirituality and how these experiences are related to their creative processes. To achieve this goal, initially, we present the concepts of spirituality and creativity, identified with the subjective aspects of human experience. Secondly, a discussion of the musician's creative processes and their relationship to the experiences of spirituality is elaborated. Then, we present the analysis of the semi-conducted interviews, in a phenomenological perspective. They have allowed further reflection on the theme of discussing music and spirituality as a way to push the boundaries as well as creative experiences